Hedging against China: formulating Canada's new strategy in the era of power politics. Issue 2 (4th May 2021) - Kawasaki, Tsuyoshi
ABSTRACT: There is an emerging consensus that Canada needs a new China strategy as its conventional approach of engagement proved to be ineffective vis-à-vis Beijing's coercive diplomacy. But what should be the central concept of such a strategy, something equivalent to engagement in the old strategy? In answering this question, the present article submits the realist concept of hedging and demonstrates that confrontation, another realist concept, is as non-viable as the liberal concept of engagement. While occupying a mid-point between these two alternatives, hedging has its own distinct features, standing on the principles of strategic literacy, soft balancing, economic pragmatism, and prudent statecraft. To develop its arguments, the article employs the concept-building and measurement approaches developed by Goertz, Gerring, and Collier et al., respectively. In addition, the article will explain why other alternative concepts such as bandwagoing and transcending should be rejected.